Cara Hidup Mahasiswi Kos di Masa Pandemi Covid-19: Apa yang Beda? - Ervina Ervina (Emik, 2022)
Corona Virus Diseases (Covid-19) is a deadly disease that hit the world at the end of 2019 and has been declared a pandemic since it was confirmed by WHO (World Health Organization) on March 11, 2020 and has spread throughout the world including Indonesia. The existence of this pandemic has an impact on every aspect of people's lives and changes people's activities, one of which is consumption patterns. One of the primary human needs is food. Food as a source of nutrition and energy for humans is one of the aspects that gets attention during the Covid-19 pandemic in order to prevent from being infected with Covid-19. How they find food when they are in the boarding houses and how they take care their immunity during pandemic Covid-19 are aspects that will be discussed in this article This research was conducted in a boarding house located boarding houses around Hasanuddin University. There are ten female students who were randomly selected and willing to be interviewed, they varied based on age, study program, and students’ hometown. Data was collected using observation and in-depth interview methods which were conducted between September 2021 and April 2022. The Covid-19 pandemic has changed almost all community activities to be more adaptive to the conditions of the Covid-19 pandemic, one of which is in the field of education. Learning activities that are usually carried out on campus, but since Covid-19 pandemic hit Indonesia, learning process was changed to online learning. Many students came back to their hometown and conducted online lectures at home. However, poor network was the main obstacle experienced by female students in the process of online learning in their village. When they came back to their boarding house, they had to readjust to the pandemic situation, including adjusting to how they find food and which kind of food they consume as well as dealing with their body immune. Female students’ preference to find food consists of four types, namely buying food directly at stalls around the boarding houses, orderingfood online, switch between buying food around boarding houses and/or ordering food online, and self cooking. In order to maintain and increase immunity, they ate healthy foods, took supplements, sunbathed, exercised, and avoided stress. During pandemi Covid-19, female students were more careful in choosing where they ordered food as well as paid special attention on how they took care their body immunity.